2011
DOI: 10.3390/f2030660
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic Review of Classical and Current Literature on the Perennial American Family Forest Problem

Abstract: Abstract:One of the fundamental issues in American forest policy has been the small forest ownership problem. Early in the twentieth century, it was called the farm forestry problem, later, the nonindustrial private forest problem, and today, the family forest problem. Family forest owners are thought to manage their lands in a suboptimal manner resulting in low forest productivity relative to other ownership groups. This can lead to future timber supply problems. The exact nature of the problem, especially it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 189 publications
(160 reference statements)
1
19
0
Order By: Relevance
“…Relationships between demographic characteristics are subtle and the model does not allow inferences about correlations between these variables (correlation does not infer causation). However, the literature suggests that landowners who are actively involved in a landowner organization or possess a professionally prepared forest management plan tend to be more abreast about issues germane to managing forestland than other groups of owners [3,9]. The historically significant variable, size of forest holding (FA), was also a good predictor of landowners' awareness of the tax incentives.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Relationships between demographic characteristics are subtle and the model does not allow inferences about correlations between these variables (correlation does not infer causation). However, the literature suggests that landowners who are actively involved in a landowner organization or possess a professionally prepared forest management plan tend to be more abreast about issues germane to managing forestland than other groups of owners [3,9]. The historically significant variable, size of forest holding (FA), was also a good predictor of landowners' awareness of the tax incentives.…”
Section: Resultsmentioning
confidence: 99%
“…Past research has found that size of forest holding is a key characteristic that is highly correlated to forest management on family forests [59]. Even the current family forest literature continues to show size of forest holding to be strongly correlated with many variables related to forest management, especially forest owners' technical knowledge and attitudes towards timber harvesting [3], making it perhaps the key variable in predicting FFO behavior. This supports the fact that the BTO variable has a substantial influence on landowners' awareness of the provisions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations